Ecstasy, Ritual, and Alternate Reality : Religion in a Pluralistic World - Goodman, Felicitas D. (Book collections on Project MUSE., 1988)
Anthropologist and spiritual explorer Felicitas Goodman offers a "unified field theory" of religion as human behavior. She examines ritual, the religious trance, alternate reality, ethics and moral code, and the named category designating religion.